“Don’t Just Do Something … Stand There!” Emergency Responders’ Peri-Incident Perceptions of Animal Owners in Bushfire - Westcott, Rachel Anne Nosworthy; Ronan, Kevin; Bambrick, Hilary; Taylor, Melanie (Frontiers in Veterinary Science, 2017)
ABSTRACT Introduction Narrowing the awareness-preparedness gap in bushfires (wildfires) means that new strategies and tactics will be needed to improve human safety and survival in this increasingly frequent and severe globally significant natural hazard. One way to do this is to explore the peri-event experiences of novel demographic groups living and working in at-risk areas to determine how best to strengthen a collaborative, mutually beneficial interface with emergency responders. Thus, this study included participants from one novel demographic, animal owners, in combination with emergency responders. Animal owners themselves are a large, diverse group whose preparedness and response behavior has not been assessed with respect to their potential contribution to contemporary natural hazard management. Method Data was collected using semi-structured interviews and focus group discussions from four emergency responder classifications who were asked about their perceptions of animal owners in bushfire. Thematic Analysis (TA) was used for data analysis because of its flexibility and suitability to this pragmatic qualitative study. Results from the first of ten themes, chosen for its ‘overview’ properties, are discussed in this paper, and indicate that exploring the animal owner – emergency responder interface has the potential to generate useful additions to public policy, and expansion of social theory. Conclusion Analysis of the data in this paper supports the potential for positive outcomes gained by reciprocal collaboration between animal owners and emergency responders. Some simple practical solutions are evident and two major outcome streams are identified. These are (1) policy development and implementation, and (2) etiology of decision-making. Considerations and recommendations for research examining the efficacy of these streams and solutions are provided.